ANALYSIS OF FINANCIAL RATIO (CAR, NPL, NIM, LDR) AND INDEPENDENT COMMISSIONERS ON PROFITABILITY IN BANKING ON THE INDONESIAN STOCK EXCHANGE - Togi Hendrik Siagian; Mochammad Chabachib (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study aims to analyze the effect of Capital Adequate Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) and Independent Commissioner on Return on Assets (ROA) in banks listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period.The research method used is a quantitative approach with testing using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The data source comes from annual reports that have been audited and submitted to the Financial Services Authority. The type of data used is secondary data based on bank financial statements.The results show that CAR and LDR have no significant effect on ROA, while NPL has a negative and significant effect on ROA, but NIM and Independent Commissioner have a positive and significant effect on ROA. This study suggests that adopting a better strategy in managing credit risk management through capital optimization, strengthening governance and can add other ratios as part of the tool to measure bank profitability performance. Keywords: Capital Adequate Ratio, Non Performing Loan, Net Interest Margin, Loan to Deposit Ratio and Independent Commissioner